Patterns of weight cycling in youth Olympic combat sports: a systematic review - Nemanja Lakicevic; Joseph J. Matthews; Guilherme G. Artioli; Antonio Paoli; Roberto Roklicer; Tatjana Trivic; Antonino Bianco; Patrik Drid (Journal of Eating Disorders, 2022)
Abstract Background Patterns of weight cycling in adult combat sports have been extensively studied, yet data on this matter in youth combat athletes is rather scarce. Methods PubMed, EBSCOhost and Web of Science were used to retrieve relevant data. Eligible studies had to record the methods used to elicit rapid weight loss (RWL) and/or record the oscillations in bodyweight during the RWL phase. Only studies conducted in the context of an official competition were considered for inclusion in the present review. Results RWL is highly prevalent in children and adolescent combat athletes, ranging from 25 to 94% depending on the type of combat sport, age and level of competition. These athletes regularly prompt RWL by increasing exercise frequency and intensity, decreasing fluid and food intake, training in impermeable suits and using sauna frequently. Overall, the magnitude of RWL was ranging from ~ 1% to 6.3 ± 3.7% with significant RWL variations within individual studies and individuals within those studies. Conclusion Acquired data indicated that RWL patterns in young combat athletes are similar to those found in their adult counterparts. Knowing that childhood and adolescence are critical periods for growth and development, RWL needs to be stringently regulated and ideally banned in this population.